Influence of green purchase intent on Love Beauty and Planet items in Padang City: green perceived value, green perceived risk, and green trust - Cehmita Siregar; Arief Maulana (Universitas Negeri Padang, 2023)
This study aims to determine whether there is an influence of green perceived value, green perceived risk and green trust on green purchase intention on love beauty and planet products in the city of Padang. The sample selection in this study used a non-purposive sampling technique and the data used in this study were primary data obtained from distributing questionnaires to 180 respondents. There are two types of data analysis techniques in this study, namely descriptive statistical analysis and inferential statistical analysis as well as hypothesis testing using SPSS 20. As a result the research states that (1) green perceived value has a positive and significant effect on green purchase intention (2) green perceived risk has a negative effect and not significant to green purchase intention, (3) green trust has a positive and significant effect on green purchase intention, (4) green perceived value, green perceived risk, and green trust simultaneously have a positive and significant effect on green purchase intention.